Protestantism and the Emergence of Human Rights = Protestantizm i zaroždenie prav čeloveka - Poll, E. W. van der (Bogoslovskie razmyšlenija, 2017)
The idea of human rights is widely accepted as a foundation of legislation and political action. It is the cornerstone of liberal democracies, the ideal held out against oppression and injustice all over the world. At the same time, it arouses debate, and criticism from all parts. Different groups fight for different causes appealing to the same principle of human rights. For all their disagreement, they could perhaps agree on one thing, that is the origin of human rights. But even then, there is disagreement. The commonly held view that human rights are the fruit of the European and American Enlightenment in the 18th century, is now being questioned. In this article, we shall see that Protestantism has played a crucial role, especially one branch of Protestantism in the English-speaking world, the Baptist movement in the early 17th century. Our interest is not only to set the historical record straight, but also to see how the particular origins of human rights are relevant for the development of this principle in today’s societies.